A RELEVÂNCIA DA EDUCAÇÃO FINANCEIRA NA FORMAÇÃO DE JOVENS - Cazella, Carla; De Brito , Thainara (Seminário de Iniciação Científica e Seminário Integrado de Ensino, Pesquisa e Extensão (SIEPE), 2021)
This article presents an analysis of financial education and itsinsertion in the lives of young people, citing the view of some experts on the subject and theexperience of academics in this environment. Objective: Identify an importance ofEducation and economics in Financial Education, understanding the perception andAcademic experiences of Unoesc Chapecó-SC and understanding the understanding ofperception of financial market professionals regarding the importance ofFinancial education for young people. Method: Research was carried out throughform with 40 questions by google forms for academics ofuniversity and insert the results found in this process through thepercentage of each answer. The research included 41 academics, carried outduring an online meeting with University professors about thefinancial education with the aim of developing this practice in the environmentfamily and take the information to the community. As results we conclude that Financial education broadens your understandingrespect for these choices. Through projects and events prepared by UNOESCthese experiences have been spreading and bringing transformations to theacademics and society.